Association between cognitive frailty and higher-level competence among community-dwelling older adults. (March 2022) - Wada, Ayumi; Makizako, Hyuma; Nakai, Yuki; Tomioka, Kazutoshi; Taniguchi, Yoshiaki; Sato, Nana; Kiuchi, Yuto; Kiyama, Ryoji; Kubozono, Takuro; Takenaka, Toshihiro; Ohishi, Mitsuru
Highlights: Cognitive frailty (CF) is comorbid physical frailty and mild cognitive impairment. Older adults should maintain higher-level competence to be independent in life. We examined associations between CF and higher-level competence in older adults. CF was associated with poor higher-level competence. CF was associated with limitations on technology usage and low social engagement. Abstract: Objectives: The purpose of this cross-sectional study was to examine the association between cognitive frailty (CF) and higher-level competence among community-dwelling older adults. Methods: Data from 871 older adults (aged ≥ 65 years, mean age 74.3 years, 61.5% women) who had participated in a community-based health check survey (Tarumizu Study 2018-2019) were analyzed. CF was defined as comorbid physical frailty and mild cognitive impairment (MCI). We defined physical frailty as either slow walking speed or poor grip strength. MCI was defined as values below the age- and education-adjusted reference threshold in several tests. Participants were categorized into four groups: robust, physical frailty, MCI, and CF. Higher-level competence was assessed using the Japan Science and Technology Agency Index of Competence (JST-IC). The JST-IC consists of 16 items and four subscales (technology usage, information practice, life management and social engagement). The bottom 20–30% score of the JST-IC and each subscale corresponded to poor higher-level competence. Results: The prevalence of CF was 14.4%. Multivariate logistic regression analysis showed that, CF was significantly associated with poor higher-level competence (odds ratio 1.92, 95% confidence interval 1.18–3.13) after adjusting for covariates. Using a similar analysis to assess the JST-IC subscales, CF was associated with limitations on technology usage (odds ratio 2.29, 95% confidence interval 1.36–3.85) and low social engagement (odds ratio 1.62, 95% confidence interval 1.00–2.61). Conclusions: This study suggests that CF is associated with poor higher-level competence, especially limitations on technology usage and low social engagement.